PENGARUH PENAMBAHAN UNSUR MAGNESIUM (MG) TERHADAP KEKERASAN DAN STRUKTUR MIKRO PADA PENGECORAN ALUMINIUM - Cholis, Setiawan Noor (Jurnal Nosel, 2013)
The objective of this research is to investigate the effect of the variations of the added magnesium (Mg) element on the hardness and micro structure of aluminum. Material for the research was aluminum. Prior to further study, aluminum was exposed to chemical composition testing to find out its composition definitely.It consisted of several phases, namely: cutting the material, smelting the material, adding the magnesium element at the Metal Laboratory, Ceper Polytechnics of Manufacture residing in Batur, Tegalrejo, Klaten. The micro structure testing and the hardness testing were conducted at the Engineering Material Laboratory, Gadjah Mada University residing at Jl. Grafika No. 2 Yogyakarta. The data of the research were analyzed by using the descriptive analytical methods. The results of the research show that the hardness value of the aluminum increases along with the quantity of the added magnesium element. The increasing amount of magnesium element added into the cast aluminum causes grain size of the aluminum to get smaller.